Properties of Uniform Fuzzy Modules and Semiuniform Fuzzy Modules - samruam baupradist; Burhan Chemat; Ronnason Chinram (IndoMS, 2022)
In this research paper, the concepts of uniform fuzzy modules and semiuniform fuzzy modules were studied. We discussed the necessary and sufficient conditions between uniform fuzzy modules (and semiuniform fuzzy modules) in fuzzy set theory and uniform modules (and semiuniform modules) in module theory.